Prototipe Alat Penghitung Ritase Pada Unit Alat Berat Secara Otomatis Berbasis IoT - Haksa, Muhammad Alif Fajri; Ariandi, Muhamad (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
Coal companies in Indonesia each year experience an increase in the amount of production that will be distributed to industries both domestically and abroad. Where some coal companies entrust other companies as contractors in terms of renting heavy equipment units to move overburden or all soil/rock that covers the coal layer. In terms of renting heavy equipment units, the contractor company will calculate the rental cost of the heavy equipment unit when carrying out mining activities by calculating the number of iterations on the heavy equipment unit used. This iteration is the number of heavy equipment work cycles in a certain time unit, sometimes the calculation of the number of iterations has a difference in calculation which results in one party experiencing a loss. Therefore, to overcome the difference in calculation, the researcher created a tool, namely the "Prototype of the Automatic IOT-Based Iteration Calculation Tool on Heavy Equipment Units" so that there is no more difference in the calculation of iterations during the mining process and the productivity of the tool will be in accordance with the planned plan.